Delavier's mixed martial arts anatomy - Delavier, Frédéric; Gundill, Michael (Champaign, IL Human Kinetics, 2013)
"More than 120 exercises and 20 training programs for the world's toughest sport"-- Cover.
Contents note continued: Beginner Basic Circuit -- Intermediate Basic Circuit -- Advanced Basic Circuit -- Customized Circuits -- Boxing Circuit -- Kicking Circuit -- Ground Fighting Circuit -- Hand-to-Hand Fighting Circuit -- Specialized Circuits At Home -- Specialized Circuit for Protecting the Neck -- Specialized Circuit for Abdominal Support -- Circuits For Injury Prevention -- Preventing Shoulder Pain -- Preventing Lower Back Pain -- Preventing Neck Pain -- Preventing Hip Pain.
Translation of: Musculation pour le fight et les sports de combat.
A revised edition of Muscularion pour le fight et les sports de combat, published in 2012 by Editions Vigot.
Keywords: Exercise -- Physiological aspects; Human anatomy; Martial arts